HEREDITARY OSTEOPETROSIS OF THE RABBIT : III. PATHOLOGIC OBSERVATIONS; SKELETAL ABNORMALITIES - Pearce, Louise (The Rockefeller University Press, 1950)
Gross and microscopic observations on the skeleton of rabbits with hereditary osteopetrosis have been described. All the bones were invariably and similarly affected. The outstanding abnormalities included the persistence of spongy bone and the presence of fibrous tissue together with the failure of development of a marrow cavity and medullary marrow. The amount of hemopoietic tissue, which was present only in comparatively small foci, was greatly reduced. The character of the lesions and their development as determined by examination of material at various stages of the disease suggested that the essential defect concerned the mesenchymal cell. The pathologic features observed generally resembled those of human osteopetrosis as did the manifestations of the disease during life (1, 2).